# Generating Function for Elementary Symmetric Function/Proof 2

## Theorem

Let $U$ be a set of $n$ numbers $\set {x_1, x_2, \ldots, x_n}$.

Let $\map {e_m} U$ be the elementary symmetric function of degree $m$ on $U$:

 $\ds \map {e_m} U$ $=$ $\ds \sum_{1 \mathop \le j_1 \mathop < j_2 \mathop < \mathop \cdots \mathop < j_m \mathop \le n} \paren {\prod_{i \mathop = 1}^m x_{j_i} }$ $\ds$ $=$ $\ds \sum_{1 \mathop \le j_1 \mathop < j_2 \mathop < \mathop \cdots \mathop < j_m \mathop \le n} x_{j_1} x_{j_2} \cdots x_{j_m}$

Let $a_m := \map {e_m} U$ for $m = 0, 1, 2, \ldots$

Let $\map G z$ be a generating function for the sequence $\sequence {a_m}$:

$\ds \map G z = \sum_{m \mathop = 0}^\infty a_m z^m$

Then:

$\ds \map G z = \prod_{k \mathop = 1}^n \paren {1 + x_k z}$

## Proof

Apply mathematical induction on $n$.

Let $\map P n$ be the statement:

 $\ds \map G z$ $\equiv$ $\ds \sum_{m \mathop = 0}^{n + 1} \map {e_m} {\set {x_1, \ldots, x_n} } z^m$ $\ds$ $=$ $\ds \prod_{k \mathop = 1}^n \paren {1 + x_k z}$

Set $U = \set {x_1}$ for $n = 1$.

Expand the formal series:

 $\ds \map G z$ $=$ $\ds \map {e_0} U + \map {e_1} U z + \sum_{m \mathop = 2}^\infty \map {e_m} U z^m$ $\ds \leadsto \ \$ $\ds$ $=$ $\ds \map {e_0} U + \map {e_1} U z$ as the summation has all zero terms $\ds \leadsto \ \$ $\ds$ $=$ $\ds 1 + x_1 z$

Then $\map P 1$ holds.

Assume $\map P n$ holds.

Let's prove $\map P {n + 1}$ holds.

The induction step uses a recursion relation:

 $\text {(1)}: \quad$ $\ds \map {e_m} {\set {x_1, \ldots, x_n, x_{n + 1} } }$ $=$ $\ds x_{n + 1} \map {e_{m - 1} } {\set {x_1, \ldots, x_n} } + \map {e_m} {\set {x_1, \ldots, x_n} }$ Recursion Property of Elementary Symmetric Function

Let $\map G z$ be defined by statement $\map P n$.

Let $\map {G^*} z$ be defined by statement $\map P {n + 1}$.

Then:

 $\ds \map {G^*} z$ $=$ $\ds \prod_{k \mathop = 1}^{n + 1} \paren {1 + x_k z}$ $\ds \leadsto \ \$ $\ds$ $=$ $\ds \map G z \paren {1 + x_{n + 1} z}$ $\ds \leadsto \ \$ $\ds$ $=$ $\ds \map G z + x_{n + 1} z \map G z$ $\ds \leadsto \ \$ $\ds$ $=$ $\ds \sum_{m \mathop = 0}^n \map {e_m} U z^m + \sum_{m \mathop = 1}^{n+1} x_{n+1} \map {e_{m-1} } U z^m$ use hypothesis $\map P n$ $\ds \leadsto \ \$ $\ds$ $=$ $\ds \map {e_0} U + \sum_{m \mathop = 1}^{n + 1} \paren {\map {e_m} U + x_{n + 1} \map {e_{m - 1} } U} z^m$ because $\map {e_{n+1} } {U} = 0$ $\ds \leadsto \ \$ $\ds$ $=$ $\ds \map {e_0} U + \sum_{m \mathop = 1}^{n + 1} \map {e_m} {\set {x_1, \ldots, x_n, x_{n + 1} } } z^m$ by recursion relation $(1)$ $\ds \leadsto \ \$ $\ds$ $=$ $\ds \sum_{m \mathop = 0}^{n + 1} \map {e_m} {\set {x_1, \ldots, x_n, x_{n + 1} } } z^m$ because $\map {e_0} X = 1$ for all sets $X$

Then $\map P {n + 1}$ holds, completing the induction.

$\blacksquare$